Towards a comparative history of comparative education: a personal journey. Issue 1 (2nd January 2020) - Manzon, Maria
ABSTRACT: Action follows from being. One's way of doing and understanding comparative education follows from one's being. It springs from the soul. Using [Kim, T., and R. Brooks' (2013). "Internationalisation, Mobile Academics, and Knowledge Creation in Universities: A Comparative Analysis." SRHE Research Award (2011/12) Final Report] framework on the relationship between academic mobility and knowledge creation, I will reflect here on my personal and intellectual journey and how it has shaped my work on comparative histories of the field of comparative education. As this article is written, I am commencing a new transition in my professional life, this time in Japan. I am reflecting on a possible new research agenda building on my past work and the new panorama opened from my new vantage point in the field.